3-D DEM installing column shape reinforcing bar element and its application for RC beam impact analysis - Fujikake, Kazunori; Katsuki, Satoshi; Haraki, Daisuke (Journal of Structural Engineering, A, 2009)
This paper proposes a column shape DEM element to use as reinforcing bar element in the reinforced concrete beam subjected to impact load. First, the rigid body motion including its posture expression is formulated as DEM equation of motion. Specialized contact judgement as reinforcing bar element which are holding semi-linear shape in the concrete materials expressed by sphere elements with rugged surface. The shear spring constitutive laws expressing the slip behavior between concrete and reinforcing bar element are also formulated. Finaly, an experimental result of RC beam subjected to weight collision impact is simulated.